2013
DOI: 10.1016/j.cemconres.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Gel nanostructure in alkali-activated binders based on slag and fly ash, and effects of accelerated carbonation

Abstract: 20Binders formed through alkali-activation of slags and fly ashes, including 'fly ash 21 geopolymers', provide appealing properties as binders for low-emissions concrete production. 22However, the changes in pH and pore solution chemistry induced during accelerated 23 carbonation testing provide unrealistically low predictions of in-service carbonation resistance. 24The aluminosilicate gel remaining in an alkali-activated slag system after accelerated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

51
369
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 701 publications
(425 citation statements)
references
References 63 publications
51
369
4
1
Order By: Relevance
“…Reflections of hematite (Fe2O3; PDF# 00-001-1053), mullite (Al6Si2O13; PDF# 00-015-0776) and quartz (SiO2; PDF# 00-033-1161) are also identified. These phases are present in the unreacted fly ash, and it has been identified that they do not participate in the alkaliactivation reaction [12,14].…”
Section: X-ray Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflections of hematite (Fe2O3; PDF# 00-001-1053), mullite (Al6Si2O13; PDF# 00-015-0776) and quartz (SiO2; PDF# 00-033-1161) are also identified. These phases are present in the unreacted fly ash, and it has been identified that they do not participate in the alkaliactivation reaction [12,14].…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…In alkaliactivated blended concretes these properties are strongly influenced by the content of fly ash incorporated [12]. Recent studies [13][14][15][16] have demonstrated that the durability of an AAC based on GGBFS/FA blends is directly linked to the microstructure of the reaction products forming in these binders, as a function of the nature and concentration of the activator, and also the maturity of the material. This is associated with the fact that the microstructure controls the transport properties of the binder and the stability of the matrix when exposed to aggressive agents.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, gel structure may vary significantly depending on the degree of reaction, curing temperature and particularly the presence of soluble silica in the activator. Duxson et al (93) analysed the nanostructure of N-A-S-H gel generated during metakaolin alkaline Studies conducted by a number of authors (37,73,(85)(86)(87) showed that both curing temperature and the nature of the activator play a significant role in reaction kinetics. While the role of the alkalis in the alkaline aluminosilicate hydrate structure is assumed to be to neutralise the excess negative charge generated by the replacement of silica tetrahedra with AlO 4 species during gel formation, scant information is available on this question.…”
Section: Fundamentals Of Alkaline Activation In Lowcalcium Systems:[(mentioning
confidence: 99%
“…This gel was also observed to contain a small amount of alkalis (normally Na), that neutralised the charge imbalance created when a Si is replaced by an Al tetrahedron. Actually, then, these are calcium-sodium aluminosilicate hydrate [C-(N)-A-S-H] gels (70)(71)(72)(73) proposed a model to describe this gel as a mix of cross-linked and non-cross-linked tobermorite-based structures (the cross-linked substituted tobermorite model, CSTM).…”
Section: Fundamentals Of Alkaline Activation In Calcium-rich Systems:mentioning
confidence: 99%
“…This can be particularly challenging due to the wide variation of chemical and physical characteristics exhibited by commercial geopolymer precursors where a range of chemical reactivity is observed, Postprint of a paper published in Powder Technology, 29(2016): [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Version of record is available at http://dx.doi.org/10.1016/j.powtec.2016.04.006 3 meaning it is often difficult to distinguish reactive from inert species.…”
Section: Introductionmentioning
confidence: 99%